Effects of a competitive soccer match on jump performance and interlimb asymmetries in elite academy soccer players - Bromley, T.; Turner, A.; Read, P.; Lake, J.; Maloney, S.; Chavda, S.; Bishop, C. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to investigate the effects of a competitive soccer match on jump performance and interlimb asymmetries over incremental time points during a 72-hour period. Fourteen elite adolescent players from a professional English category 3 academy performed single-leg countermovement jumps pre, post, 24-, 48-, and 72-hour post-match on a single force platform. Eccentric impulse, concentric impulse, peak propulsive force, jump height, peak landing force, and landing impulse were monitored throughout. Interlimb asymmetries were also calculated for each metric as the percentage difference between limbs. Significant negative changes (p < 0.05) in jump performance were noted for all metrics at all time points, with the exception of jump height. Interlimb asymmetries were metric-dependent and showed very large increases, specifically post-match, with a trend to reduce back toward baseline values at the 48-hour time point for propulsive-based metrics. Asymmetries for landing metrics did not peak until the 24-hour time point and again reduced toward baseline at 48-hour time point. This study highlights the importance of monitoring distinct jump metrics, as jump height alone was not sensitive enough to show significant changes in jump performance. However, interlimb asymmetries were sensitive to fatigue with very large increases post-match. More frequent monitoring of asymmetries could enable practitioners to determine whether existing imbalances are also associated with reductions in physical performance or increased injury risk.